Percutaneous Flexible Double Pinning (Py–Desmanet's Procedure) for Pediatric Distal Radius Fractures. (December 2013) - Sano, Kazufumi; Hashimoto, Tomohisa; Kimura, Kazumasa; Ozeki, Satoru
Purpose: The purpose of this study is to report the results of percutaneous flexible double pinning for pediatric distal radius fractures. Methods: Thirteen unstable fractures (three physeal and ten metaphyseal) of the distal radius in which the physeal plate could be still identified were treated with percutaneous flexible double pinning between 2008 and 2011. The average age of these cases was 9.8 years (range, 2–16 years). According as Py–Demanet's original technique, the fracture was fixed with two percutaneous transepiphyseal intramedullary wires. Kirschner wires or c-wires of 1.4–1.6 mm in diameter were used in each case depending on age. Operative and short follow-up outcomes were assessed. Results: The average operative duration was 23 min (range, 5–45 min). Comorbid distal ulnar fractures were further stabilized by intramedullary pinning. Additional external splintage was administered in all cases for 6 weeks postoperatively. Wires were removed after an average of 7.2 weeks (range, 4–10 weeks). Bone union was achieved in all cases. Neither malunion nor early epiphyseal closure of the distal radius was identified at mean follow-up of 12 months (range, 3–51 months). Discussion: Flexible double pinning has been successfully used for distal radius fractures in adults. Since this technique is minimally invasive, quick, and technically easy, it is also a good treatment option for unstable distal radius fractures in children. Level of clinical evidence: Therapeutic Level IV